A novel molecularly imprinted polymer-solid phase extraction method coupled with high performance liquid chromatography tandem mass spectrometry for the determination of nitrosamines in water and beverage samples. (15th September 2019) - Li, Zhigang; Wang, Junjie; Chen, Xiao; Hu, Shaoyang; Gong, Tingting; Xian, Qiming
Highlights: Molecularly imprinted polymers (MIPs) were firstly synthesized for Nitrosamines. The MIPs had high selectivity and satisfactory recoveries for analysis of NAs. The new method has lower limit of detection (0.2–0.7 ng/L) of NAs. The new method has been successfully applied to analysis of NAs in real samples. Abstract: Nitrosamines (NAs) as a group of emerging nitrogenous disinfection byproducts were present in drinking water at ng/L levels. Accurate measurements of NAs at such a trace level in samples is a challenging task. Solid phase extraction (SPE), which is used in the sample pretreatment, plays a critical role in the analysis of NAs in water. In this study, a highly selective and sensitive method for the determination of five less polar NAs, namely nitrosodiethylamine nitrosopiperidine, nitrosodi-n-propylamine, nitrosodibutylamine and nitrosodiphenylamine, in water and beverage samples was developed. A new molecularly imprinted polymer (MIP) was synthesized and used as sorbents in SPE for the sample preparation. Prepared samples were analyzed using high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). Satisfactory recoveries were obtained at three different concentrations (5, 20, and 50 ng/L, n = 3) in the range of 93–107% with relative standard deviations of 3.1–9.8%. Limit of detection and limit of quantitation for the five NAs were in the range of 0.2–0.7 ng/L and 0.6–2.1 ng/L, respectively. Method precisions ranged from 4.9% to 10.5%. This novel method of MIP-SPE coupled with HPLC-MS/MS was successfully applied to the determination of these five NAs in different types of water and beverages samples.